Measurement and data analysis for engineering and science - Dunn, Patrick F. (McGraw-Hill Higher Education, 2005)
Dunn's Measurement and Data Analysis for Engineering & Science offers an up-to-date, practical approach to learning and implementing lab skills, technical reporting, and data analysis. Its engaging writing style, use of historical vignettes, and numerous learning features make it the best book available for students. The first three chapters of the text cover the basics--experimental methods, units & significant figures, technical communications and basic electronics. Hardware issues are then presented, with a focus on measurement systems, and calibration & response. The final chapters deal with data analysis, with an overview of basic probability & statistics, uncertainty analysis, signal characteristics, and digital signal analysis. Following the text chapters, a full laboratory manual, with an introduction and twelve lab experiments, is included. This gives users a chance to put their basic skills to work in actual engineering experiments, which are taken from a variety of engineering subject areas.